Pengembangan Kampung Matara Melalui Pendampingan Literasi Sadar Hukum dan Penanaman Pendidikan Karakter - Nurul Widhanita Y. Badilla; Rezky Uspayanti (PT. Akselerasi Karya Mandiri, 2024)
The Community Service aims to develop Matara Village through legal awareness literacy assistance and character building. This activity has been carried out by involving the society of Matara village. It was done to overcome the partner issues. The method used was through socialization and practice which consists of several stages; preparation stage, drafting stage, mentoring stage, and evaluation stage. The preparation stage consists of licensing and observation to unite the perception of the service team with partners regarding the objectives and technical implementation of activities. The second stage is the preparation of a draft module that will be used during the implementation of activities related to legal literacy and character education. The module is related to basic language learning associated with local wisdom. The module is presented in a language that is easier to understand and according to the needs of partners. The third stage of this activity is the mentoring stage which is carried out in 2 stages, namely focusing on language learning in increasing legal literacy and socializing the importance of character education based on local wisdom. The last stage is the evaluation by looking at the output of the sustainability of the results of the activity without assistance. This activity received a positive response from the society of Matara Village.